Applying the Hadith on Cleanliness in Eco-Theological Islamic Education at Community Learning Centers (PKBM): Penerapan Hadis Kebersihan dalam Pembelajaran PAI Berbasis Ekoteologi di Pusat Kegiatan Belajar Masyarakat (PKBM) - Murtadoilah, Hendi; Rusmidi, Didi (Journal of Society and Development, 2025)
Islamic Religious Education (PAI) in Community Learning Centers (PKBM) plays a strategic role in instilling religious values while fostering social and ecological awareness among learners. In the context of the global environmental crisis, an ecotheological approach offers a relevant alternative to strengthen spirituality oriented toward environmental preservation. This study aims to examine the implementation of a hadith on cleanliness, particularly the hadith "At-thuhūru syathrul īmān" (cleanliness is part of faith), within ecotheology-based PAI learning at PKBM Harmoni, Cirebon, West Java. This research employs a descriptive qualitative method, using data collection techniques such as observation, in-depth interviews with tutors and learners, and documentation analysis of teaching materials. The data were analyzed using the interactive analysis model of Miles and Huberman. The results show that integrating spiritual and ecological values into PAI learning enhances eco-faith awareness, strengthens religious attitudes, and encourages learners to take real actions in maintaining cleanliness and caring for the environment. This study contributes to the development of a contextual and transformative model of Islamic education in non-formal learning settings and opens up possibilities for integrating ecotheology into character education and environmental awareness based on Islamic values.